Climate Change Adaptation Communication in Bangladesh: A study on village and wetland women of Jamalpur - Aurthy Noboneeta (Informasi, 2025)
With a focus on the experiences of rural and wetland women in Jamalpur, this study examines the vulnerabilities that women confront in the context of climate change. Based on a theoretical framework that includes concepts of innovation, crisis communication theory, social network theory and capability approach. The study uses in-depth interviews with 13 village and wetland women, and separate focused group discussions among them, and seven key informant interviews. Results show that women demonstrate resilience in the face of a lack of understanding about climate change and the dangers it poses by applying their local knowledge and experiences to adapt to difficult situations. Wetland women's communication patterns are notably different from village women's, suggesting differences in social practices. It would seem that village women are in a more privileged position and could have better access to resources and information. This study highlights the value of support networks and communication tools while illuminating women's ability to adjust to climate-related issues. The results highlight the necessity of customized interventions that identify and tackle the distinct vulnerabilities faced by women in various social and geographic contexts, ultimately leading to more efficacious measures for adapting to climate change.